1985
DOI: 10.1016/s0022-5347(17)47640-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Complexes and Immunosuppressive Acidic Protein in Patients with Renal Cell Carcinoma

Abstract: Sera from 23 patients with renal cell carcinoma were tested for circulating immune complexes by Clq binding assay and immunosuppressive acidic protein by single radial immunodiffusion. The mean values of circulating immune complexes and immunosuppressive acidic protein in the patients were significantly higher than those of normal controls, and over-all positive rates were 52 and 35 per cent, respectively. There was a significant correlation between immunosuppressive acidic protein levels and the extent of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…IAP is a nonspecific protein for renal cell carcinomas, however, some authors reported its usefulness as a tumor marker for these tumors [10][11][12], In this study, we esti mated serum IAP levels in 143 patients. Briefly, we came to the result that serum IAP levels clearly corresponded to tumor volumes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…IAP is a nonspecific protein for renal cell carcinomas, however, some authors reported its usefulness as a tumor marker for these tumors [10][11][12], In this study, we esti mated serum IAP levels in 143 patients. Briefly, we came to the result that serum IAP levels clearly corresponded to tumor volumes.…”
Section: Discussionmentioning
confidence: 91%
“…Some investigators stressed the suitability of IAP as a tumor marker for renal cell carcinoma [10][11][12], In this study, we tested this statement.…”
Section: Introductionmentioning
confidence: 93%
“…Many investigators have reported that serum IAP is useful for monitoring the recurrence of cancer and response to therapy. 13–17 It has also been reported that the DNA content is of predictive importance; aneuploidy was found to be associated with high proliferation, local tumor invasion and poor prognosis. Furthermore, distinct chromosomal changes were also shown to be related to tumor progression in RCC.…”
Section: Introductionmentioning
confidence: 97%
“…Among patients treated at Hamamatsu University School There are no specific tumour markers for RCC, although advanced RCC is reported to be associated with an of Medicine and related hospitals from 1983 to 1995, 133 with RCC (mean age 60.1 years, sd 11.4, range increase of immunosuppressive acidic protein (IAP) [1][2][3] and IAP has been found useful for detecting the 31-84) in whom serum IAP was measured before treatment were selected. The pathological stage was recurrence of RCC after surgery [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The serum IAP value is reported to increase in patients with RCC [2] and IAP positivity is associated with a determined and compared with the predictive value of the other four analytes. Tumour size was calculated more advanced stage and size of the cancer [1][2][3]. Elevation of IAP is reportedly useful for detecting recur-from ultrasonography, CT, MRI, or angiography in 127 patients, and was confirmed from the resected specimen.…”
Section: Introductionmentioning
confidence: 99%